Optimal operation of storage systems in distribution networks considering battery degradation - Macedo, Leonardo H. [UNESP]; Ortega-Vazquez, Miguel A.; Romero, Ruben [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Energy storage systems are lauded solutions for integrating the ever-increasing amounts of renewable energy sources in distribution networks. Electrochemical batteries, principally lithium-ion based, are among the most promising storage technologies for these applications due their high energy densities, capacities, and efficiencies. The operation of these energy storage resources must be optimized since every charge/discharge cycle wears the battery and reduces its lifespan. This paper presents a stochastic second-order cone programming model, that considers the AC power flow equations, for optimizing the operation of battery storage systems in distribution networks, taking into account their degradation characteristics explicitly. A 33-node distribution network is used to demonstrate the effectiveness of the proposed method. Results also demonstrate the importance of including the degradation characteristics in the model, in order to attain solutions that strike a balance between operating costs and the benefits of prolonging the lifespan of the batteries.
Keywords: Battery storage systems; Distribution networks; Photovoltaic generation; Second-order cone programming; Stochastic optimization